Analyze of Leachate Composition in the Dumpsites of East-Latgale Region (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
There are are 28 working or closed but not recultivated municipal solid waste dumpsites in East-Latgale now. A number of these dumpsites are situated near lakes, rivers, in old mineral quarries etc [3, 6]. All these dumpsites pollute groundwater, soil and present danger for human health. One of the dangerous factors is leachate which is generated in these dumpsites and which pollutes groundwate, soil and drinking water. The analysis of leachate sample chemical content in the biggest East-Latgale dumpsites “Ritini”, “Zvirgzdene”, “Zelceva” and “Mostovaja” has been done in 2002. The content of leachate depends on content of waste, dumpsite management etc. The most polluted leachate is in the biggest dumpsites of region – “Ritini” and “Zvirgzdene”. These are city dumpsites (Rezekne and Ludza). Significantly less polluted leachate is found in the dumpsites “Zelceva” and “Mostovaja”. This is valid for all analyzed parameters – COD, conductivity, Ntot., NH4 + and Cl.